Simulasi Rangka Engine Trainer dengan Lengan Adaptor sebagai Penunjang Pembelajaran Assembly dan Disassembly - Misbakhul Fatah; Rahman Hakim; Auliana Diah Wilujeng; Sayyid Hasan (Infotekmesin, 2022)
Overhaul is a method of engine maintenance where the engine is dismantled and all components are checked and replaced if there is damage. In carrying out overhaul activities, engine trainer  tools are needed, therefore the operator can reach the components in the pinch point. Engine trainers on the market are usually only specific to one engine. However, in this study, a universal engine trainer was designed with various adapter arms that can rotate on one axis. This engine trainer is equipped with a buffer that is useful for reducing vibration when the engine is started. The design of the engine trainer frame was tested for strength using a static load simulation with an engine load of 400 N. The simulation showed that the frame deflection due to the load was 0.7781 mm. This value can be said to be safe from a static load test.